finding sum of tree to list using haskell - haskell

I am trying to apply sum using id function while giving input to program.but i am with below. any guidance is much appreciated.
data Tree a = Leaf a | Node (Tree a) a (Tree a) deriving (Eq, Show)
reduce_tree :: Tree a -> (a -> b) -> (b -> a -> b -> b) -> b
reduce_tree (Leaf v) = [v]
reduce_tree (Node left root right) = reduce_tree left ++ [root] ++ reduce_tree right
input as follows:
ghci> reduce_tree (VNode (VLeaf 1) 2 (VNode (VLeaf 3) 4 (VLeaf 5)))
id sum
where sum t1 v t2 = t1 + v + t2
15

Since I don't understand your question completely, here are some observations:
reduce_tree's type signature suggests that it should have more arguments than you give it.
If f is a function that maps values of type a to values of type b, and g is what appears to be an accumulating function of three arguments (although I'm unsure why two are not enough), then
reduce_tree :: Tree a -> (a -> b) -> (b -> a -> b -> b) -> b
reduce_tree (Leaf v) f g = ...
reduce_tree (Node left v right) f g = ...
If reduce_tree is in fact a reduce function, and not one that simply flattens trees into lists, you may draw inspiration from Data.Foldable.
data Tree a = Leaf a | Node (Tree a) a (Tree a) deriving (Show, Eq)
treefold :: (a -> b -> b) -> b -> Tree a -> b
treefold f acc (Leaf x) = f x acc
treefold f acc1 (Node left x right) =
let acc2 = treefold f acc1 right
acc3 = f x acc2
acc4 = treefold f acc3 left
in acc4
With such a function you can either flatten or sum the elements of a tree:
flattenTree :: Tree a -> [a]
flattenTree tree = treefold (:) [] tree
sumTree :: Num a => Tree a -> a
sumTree tree = treefold (+) 0 tree
The only bell that rings when you say "apply sum using id function" is that perhaps you wish to use continuations. This is already covered thoroughly in e.g. Haskell: tail recursion version of depth of binary tree and concisely in Tail-recursion on trees (Standard ML). A Haskell equivalent would be:
treefold :: (a -> b -> b) -> b -> Tree a -> b
treefold f acc tree = tf f acc tree id
where
tf f acc (Leaf x) k = k (f x acc)
tf f acc (Node left x right) old_k = tf f left acc new_k
where
new_k = \acc -> tf f right (f x acc) old_k
Now sumTree can be defined in the exact same way as before, except it would use folding as well as the identity function as the initial continuation. Or you could extract the helper function tf to the top-level if you want to feed the traversal function with the function id yourself.

Oh, if I understand correctly, I think you are just trying to enter your example into ghci. I would recommend putting the complexity in the file:
sum_tree :: Tree Int -> Int
sum_tree t = reduce_tree t id sum
where sum t1 v t2 = t1 + v + t2
then in ghci, after you have loaded the file that sum_tree and reduce_tree are defined in,
ghci> sum_tree (VNode (VLeaf 1) 2 (VNode (VLeaf 3) 4 (VLeaf 5))
If you must do it all in ghci, be aware that you can't use where in ghci usually, since where is only used in definitions. Use let ... in instead:
ghci> let sum t1 v t2 = t1 + v + t2 in reduce_tree (VNode (VLeaf 1) 2 (VNode (VLeaf 3) 4 (VLeaf 5))) id sum
If you for some reason don't want to use let, you can use a lambda:
ghci> reduce_tree (VNode (VLeaf 1) 2 (VLeaf 3)) id (\t1 v t2 -> t1 + v + t2)
Did I understand your question correctly?

Related

Haskell - Create a fold function for tree type

I have this simple data Tree :
data Tree = Leaf Int | Node [Tree]
And I have to devellop a fold function for this type :
foldTree :: (Int -> a) -> ([a] -> a) -> Tree -> a
for example :
foldTree (+1) sum (Node[ (Leaf 2), (Leaf 3)])
will return (2+1)+(3+1) = 7
For leafs, I have :
foldTree f g (Leaf n) = (f n)
But I have no ideas for develop the nodes's case.
I'm french, also sorry for the mistakes.
It sometimes helps to look at what is available in scope and their types. Here's a solution:
foldTree f g (Leaf n) = (f n)
foldTree f g (Node subtrees) =
let as = map (foldTree f g) subtrees -- as :: [a]
in g as

How to lift a fold|map|both into the Either monad?

A "map" of type
mapIsh :: Traversable t => (a -> Either b c) -> t a -> Either b (t c)
would be a start. (Hayoo doesn't find one.) Or a "fold" of type
foldIsh :: (b -> a -> Either l b) -> b -> t a -> Either l b
Best of all (for my case) would be this:
mapAccumIsh :: (a -> b -> Either l (a, c)) -> a -> t b -> Either l (a, t c)
That might be all you need to read. In case you want more details, though, here's a concrete example:
Imagine a treelike structure to mapAccum over. Each branch, after evaluating its children, gets transformed by some function of its children and the accumulator.
Here's some working code that adds each Tree's value to the accumulator, and also adds to each Branch's label the product of its childrens' labels:
module Temp where
import Data.List
data Tree = Leaf Float | Branch Float [Tree] deriving (Show)
label :: Tree -> Float
label (Leaf i) = i
label (Branch i _) = i
f :: Float -> Tree -> (Float, Tree)
f i (Leaf j) = (i+j, Leaf j)
f i (Branch j ts) = (i + tf, Branch tf ts2) where
(i2, ts2) = mapAccumL f i ts
tf = j + (foldl (*) 1 $ map label ts2)
-- the problem: what if instead of (*) in the line above, we used this?
evenMult :: Float -> Float -> Either String Float
evenMult a b = case even $ round b of True -> Right $ a * b
False -> Left "that's odd"
go = f 0 $ Branch 2 [Branch 2 [Leaf 2]
,Branch 2 [Leaf 2, Leaf (-2)]]
Here's what that returns:
(-6.0,Branch (-6.0) [Branch 4.0 [Leaf 2.0]
,Branch (-2.0) [Leaf 2.0,Leaf (-2.0)]])
But what if, instead of using (*) in the foldl, we used evenMult?

Expression expansion using recursion schemes

I have a data type representing arithmetic expressions:
data E = Add E E | Mul E E | Var String
I want to write an expansion function which will convert an expression into sum of products of variables (sort of braces expansion). Using recursion schemes of course.
I only could think of an algorithm in the spirit of "progress and preservation". The algorithm at each step constructs terms that are fully expanded so there is no need to re-check.
The handling of Mul made me crazy, so instead of doing it directly I used an isomorphic type of [[String]] and took advantage of concat and concatMap already implemented for me:
type Poly = [Mono]
type Mono = [String]
mulMonoBy :: Mono -> Poly -> Poly
mulMonoBy x = map (x ++)
mulPoly :: Poly -> Poly -> Poly
mulPoly x = concatMap (flip mulMonoBy x)
So then I just use cata:
expandList :: E -> Poly
expandList = cata $ \case
Var x -> [[x]]
Add e1 e2 = e1 ++ e2
Mul e1 e2 = mulPoly e1 e2
And convert back:
fromPoly :: Poly -> Expr
fromPoly = foldr1 Add . map fromMono where
fromMono = foldr1 Mul . map Var
Are there significantly better approaches?
Upd: There are few confusions.
The solution does allow multiline variable names. Add (Val "foo" (Mul (Val "foo) (Var "bar"))) is a representation of foo + foo * bar. I'm not representing x*y*z with Val "xyz" or something. Note that also as there are no scalars repeated vars such as "foo * foo * quux" are perfectly allowed.
By sum of products I mean sort of "curried" n-ary sum of products. A concise definition of sum of products is that I want an expression without any parentheses, with all parens represented by associativity and priority.
So (foo * bar + bar) + (foo * bar + bar) is not a sum of products as the because of middle + is sum of sums
(foo * bar + (bar + (foo * bar + bar))) or corresponding left-associative version are right answers, although we must guarantee that associativity is always left of always right. So the correct type for right-assoaciative solution is
data Poly = Sum Mono Poly
| Product Mono
which is isomorphic to nonempty lists: NonEmpty Poly (note Sum Mono Poly instead of Sum Poly Poly). If we allow empty sums or products then we get just the list of list representation I used.
Also of you don't care about performance, the multiplication seems to be just liftA2 (++)
I am no expert in recursion schemes, but since it sounds like you are trying to practice them, hopefully you will not find it too onerous to convert a solution using manual recursion to one using recursion schemes. I'll write it with mixed prose and code first, and include the complete code again at the end for simpler copy/pasting.
It is not too difficult to do using simply the distributive property and a bit of recursive algebra. Before we begin, though, let's define a better result type, one that guarantees we can only ever represent sums of products:
data Poly term = Sum (Poly term) (Poly term)
| Product (Mono term)
deriving Show
data Mono term = Term term
| MonoMul (Mono term) (Mono term)
deriving Show
This way we can't possibly mess up and accidentally yield an incorrect result like
(Mul (Var "x") (Add (Var "y") (Var "z")))
Now, let's write our function.
expand :: E -> Poly String
First, a base case: it is trivial to expand a Var, because it is already in sum-of-products form. But we must convert it a bit to fit it into our Poly result type:
expand (Var x) = Product (Term x)
Next, note that it is easy to expand an addition: simply expand the two sub-expressions, and add them together.
expand (Add x y) = Sum (expand x) (expand y)
What about a multiplication? That is a bit more complicated, since
Product (expand x) (expand y)
is ill-typed: we can't multiply polynomials, only monomials. But we do know how to do algebraic manipulation to turn a multiplication of polynomials into a sum of multiplications of monomials, via the distributive rule. As in your question, we'll need a function mulPoly. But let's just assume that exists, and implement it later.
expand (Mul x y) = mulPoly (expand x) (expand y)
That handles all the cases, so all that's left is to implement mulPoly by distributing the multiplications across the two polynomials' terms. We simply break down one of the polynomials one term at a time, and multiply the term across each of the terms in the other polynomial, adding together the results.
mulPoly :: Poly String -> Poly String -> Poly String
mulPoly (Product x) y = mulMonoBy x y
mulPoly (Sum a b) x = Sum (mulPoly a x) (mulPoly b x)
mulMonoBy :: Mono String -> Poly -> Poly
mulMonoBy x (Product y) = Product $ MonoMul x y
mulMonoBy x (Sum a b) = Sum (mulPoly a x') (mulPoly b x')
where x' = Product x
And in the end, we can test that it works as intended:
expand (Mul (Add (Var "a") (Var "b")) (Add (Var "y") (Var "z")))
{- results in: Sum (Sum (Product (MonoMul (Term "y") (Term "a")))
(Product (MonoMul (Term "z") (Term "a"))))
(Sum (Product (MonoMul (Term "y") (Term "b")))
(Product (MonoMul (Term "z") (Term "b"))))
-}
Or,
(a + b)(y * z) = ay + az + by + bz
which we know to be correct.
The complete solution, as promised above:
data E = Add E E | Mul E E | Var String
data Poly term = Sum (Poly term) (Poly term)
| Product (Mono term)
deriving Show
data Mono term = Term term
| MonoMul (Mono term) (Mono term)
deriving Show
expand :: E -> Poly String
expand (Var x) = Product (Term x)
expand (Add x y) = Sum (expand x) (expand y)
expand (Mul x y) = mulPoly (expand x) (expand y)
mulPoly :: Poly String -> Poly String -> Poly String
mulPoly (Product x) y = mulMonoBy x y
mulPoly (Sum a b) x = Sum (mulPoly a x) (mulPoly b x)
mulMonoBy :: Mono String -> Poly String -> Poly String
mulMonoBy x (Product y) = Product $ MonoMul x y
mulMonoBy x (Sum a b) = Sum (mulPoly a x') (mulPoly b x')
where x' = Product x
main = print $ expand (Mul (Add (Var "a") (Var "b")) (Add (Var "y") (Var "z")))
This answer has three sections. The first section, a summary in which I present my two favourite solutions, is the most important one. The second section contains types and imports, as well as extended commentary on the way towards the solutions. The third section focuses on the task of reassociating expressions, something that the original version of the answer (i.e. the second section) had not given due attention.
At the end of the day, I ended up with two solutions worth discussing. The first one is expandDirect (cf. the third section):
expandDirect :: E a -> E a
expandDirect = cata alg
where
alg = \case
Var' s -> Var s
Add' x y -> apo coalgAdd (Add x y)
Mul' x y -> (apo coalgAdd' . apo coalgMul) (Mul x y)
coalgAdd = \case
Add (Add x x') y -> Add' (Left x) (Right (Add x' y))
x -> Left <$> project x
coalgAdd' = \case
Add (Add x x') y -> Add' (Left x) (Right (Add x' y))
Add x (Add y y') -> Add' (Left x) (Right (Add y y'))
x -> Left <$> project x
coalgMul = \case
Mul (Add x x') y -> Add' (Right (Mul x y)) (Right (Mul x' y))
Mul x (Add y y') -> Add' (Right (Mul x y)) (Right (Mul x y'))
x -> Left <$> project x
With it, we rebuild the tree from the bottom (cata). On every branch, if we find something invalid we walk back and rewrite the subtree (apo), redistributing and reassociating as needed until all immediate children are correctly arranged (apo makes it possible to do that without having to rewrite everyting down to the very bottom).
The second solution, expandMeta, is a much simplified version of expandFlat from the third section.
expandMeta :: E a -> E a
expandMeta = apo coalg . cata alg
where
alg = \case
Var' s -> pure (Var s)
Add' x y -> x <> y
Mul' x y -> Mul <$> x <*> y
coalg = \case
x :| [] -> Left <$> project x
x :| (y:ys) -> Add' (Left x) (Right (y :| ys))
expandMeta is a metamorphism; that is, a catamorphism followed by an anamorphism (while we are using apo here as well, an apomorphism is just a fancy kind of anamorphism, so I guess the nomenclature still applies). The catamorphism changes the tree into a non-empty list -- that implicitly handles the reassociation of the Adds -- with the list applicative being used to distribute multiplication (much like you suggest). The coalgebra then quite trivially converts the non-empty list back into a tree with the appropriate shape.
Thank you for the question -- I had a lot of fun with it! Preliminaries:
{-# LANGUAGE LambdaCase #-}
{-# LANGUAGE TypeFamilies #-}
{-# LANGUAGE DeriveFunctor #-}
{-# LANGUAGE DeriveFoldable #-}
{-# LANGUAGE GeneralizedNewtypeDeriving #-}
import Data.Functor.Foldable
import qualified Data.List.NonEmpty as N
import Data.List.NonEmpty (NonEmpty(..))
import Data.Semigroup
import Data.Foldable (toList)
import Data.List (nub)
import qualified Data.Map as M
import Data.Map (Map, (!))
import Test.QuickCheck
data E a = Var a | Add (E a) (E a) | Mul (E a) (E a)
deriving (Eq, Show, Functor, Foldable)
data EF a b = Var' a | Add' b b | Mul' b b
deriving (Eq, Show, Functor)
type instance Base (E a) = EF a
instance Recursive (E a) where
project = \case
Var x -> Var' x
Add x y -> Add' x y
Mul x y -> Mul' x y
instance Corecursive (E a) where
embed = \case
Var' x -> Var x
Add' x y -> Add x y
Mul' x y -> Mul x y
To begin with, my first working (if flawed) attempt, which uses the applicative instance of (non-empty) lists to distribute:
expandTooClever :: E a -> E a
expandTooClever = cata $ \case
Var' s -> Var s
Add' x y -> Add x y
Mul' x y -> foldr1 Add (Mul <$> flatten x <*> flatten y)
where
flatten :: E a -> NonEmpty (E a)
flatten = cata $ \case
Var' s -> pure (Var s)
Add' x y -> x <> y
Mul' x y -> pure (foldr1 Mul (x <> y))
expandTooClever has one relatively serious problem: as it calls flatten, a full-blown fold, for both subtrees whenever it reaches a Mul, it has horrible asymptotics for chains of Mul.
Brute force, simplest-thing-that-could-possibly-work solution, with an algebra that calls itself recursively:
expandBrute :: E a -> E a
expandBrute = cata alg
where
alg = \case
Var' s -> Var s
Add' x y -> Add x y
Mul' (Add x x') y -> Add (alg (Mul' x y)) (alg (Mul' x' y))
Mul' x (Add y y') -> Add (alg (Mul' x y)) (alg (Mul' x y'))
Mul' x y -> Mul x y
The recursive calls are needed because the distribution might introduce new occurrences of Add under Mul.
A slightly more tasteful variant of expandBrute, with the recursive call factored out into a separate function:
expandNotSoBrute :: E a -> E a
expandNotSoBrute = cata alg
where
alg = \case
Var' s -> Var s
Add' x y -> Add x y
Mul' x y -> dis x y
dis (Add x x') y = Add (dis x y) (dis x' y)
dis x (Add y y') = Add (dis x y) (dis x y')
dis x y = Mul x y
A tamed expandNotSoBrute, with dis being turned into an apomorphism. This way of phrasing it expresses nicely the big picture of what is going on: if you only have Vars and Adds, you can trivially reproduce the tree bottom-up without a care in the world; if you hit a Mul, however, you have to go back and reconstuct the whole subtree to perform the distributions (I wonder is there is a specialised recursion scheme that captures this pattern).
expandEvert :: E a -> E a
expandEvert = cata alg
where
alg :: EF a (E a) -> E a
alg = \case
Var' s -> Var s
Add' x y -> Add x y
Mul' x y -> apo coalg (x, y)
coalg :: (E a, E a) -> EF a (Either (E a) (E a, E a))
coalg (Add x x', y) = Add' (Right (x, y)) (Right (x', y))
coalg (x, Add y y') = Add' (Right (x, y)) (Right (x, y'))
coalg (x, y) = Mul' (Left x) (Left y)
apo is necessary because we want to anticipate the final result if there is nothing else to distribute. (There is a way to write it with ana; however, that requires wastefully rebuilding trees of Muls without changes, which leads to the same asymptotics problem expandTooClever had.)
Last, but not least, a solution which is both a successful realisation of what I had attempted with expandTooClever and my interpretation of amalloy's answer. BT is a garden-variety binary tree with values on the leaves. A product is represented by a BT a, while a sum of products is a tree of trees.
expandSOP :: E a -> E a
expandSOP = cata algS . fmap (cata algP) . cata algSOP
where
algSOP :: EF a (BT (BT a)) -> BT (BT a)
algSOP = \case
Var' s -> pure (pure s)
Add' x y -> x <> y
Mul' x y -> (<>) <$> x <*> y
algP :: BTF a (E a) -> E a
algP = \case
Leaf' s -> Var s
Branch' x y -> Mul x y
algS :: BTF (E a) (E a) -> E a
algS = \case
Leaf' x -> x
Branch' x y -> Add x y
BT and its instances:
data BT a = Leaf a | Branch (BT a) (BT a)
deriving (Eq, Show)
data BTF a b = Leaf' a | Branch' b b
deriving (Eq, Show, Functor)
type instance Base (BT a) = BTF a
instance Recursive (BT a) where
project (Leaf s) = Leaf' s
project (Branch l r) = Branch' l r
instance Corecursive (BT a) where
embed (Leaf' s) = Leaf s
embed (Branch' l r) = Branch l r
instance Semigroup (BT a) where
l <> r = Branch l r
-- Writing this, as opposed to deriving it, for the sake of illustration.
instance Functor BT where
fmap f = cata $ \case
Leaf' x -> Leaf (f x)
Branch' l r -> Branch l r
instance Applicative BT where
pure x = Leaf x
u <*> v = ana coalg (u, v)
where
coalg = \case
(Leaf f, Leaf x) -> Leaf' (f x)
(Leaf f, Branch xl xr) -> Branch' (Leaf f, xl) (Leaf f, xr)
(Branch fl fr, v) -> Branch' (fl, v) (fr, v)
To wrap things up, a test suite:
newtype TestE = TestE { getTestE :: E Char }
deriving (Eq, Show)
instance Arbitrary TestE where
arbitrary = TestE <$> sized genExpr
where
genVar = Var <$> choose ('a', 'z')
genAdd n = Add <$> genSub n <*> genSub n
genMul n = Mul <$> genSub n <*> genSub n
genSub n = genExpr (n `div` 2)
genExpr = \case
0 -> genVar
n -> oneof [genVar, genAdd n, genMul n]
data TestRig b = TestRig (Map Char b) (E Char)
deriving (Show)
instance Arbitrary b => Arbitrary (TestRig b) where
arbitrary = do
e <- genExpr
d <- genDict e
return (TestRig d e)
where
genExpr = getTestE <$> arbitrary
genDict x = M.fromList . zip (keys x) <$> (infiniteListOf arbitrary)
keys = nub . toList
unsafeSubst :: Ord a => Map a b -> E a -> E b
unsafeSubst dict = fmap (dict !)
eval :: Num a => E a -> a
eval = cata $ \case
Var' x -> x
Add' x y -> x + y
Mul' x y -> x * y
evalRig :: (E Char -> E Char) -> TestRig Integer -> Integer
evalRig f (TestRig d e) = eval (unsafeSubst d (f e))
mkPropEval :: (E Char -> E Char) -> TestRig Integer -> Bool
mkPropEval f = (==) <$> evalRig id <*> evalRig f
isDistributed :: E a -> Bool
isDistributed = para $ \case
Add' (_, x) (_, y) -> x && y
Mul' (Add _ _, _) _ -> False
Mul' _ (Add _ _, _) -> False
Mul' (_, x) (_, y) -> x && y
_ -> True
mkPropDist :: (E Char -> E Char) -> TestE -> Bool
mkPropDist f = isDistributed . f . getTestE
main = mapM_ test
[ ("expandTooClever" , expandTooClever)
, ("expandBrute" , expandBrute)
, ("expandNotSoBrute", expandNotSoBrute)
, ("expandEvert" , expandEvert)
, ("expandSOP" , expandSOP)
]
where
test (header, func) = do
putStrLn $ "Testing: " ++ header
putStr "Evaluation test: "
quickCheck $ mkPropEval func
putStr "Distribution test: "
quickCheck $ mkPropDist func
By sum of products I mean sort of "curried" n-ary sum of products. A concise definition of sum of products is that I want an expression without any parentheses, with all parens represented by associativity and priority.
We can adjust the solutions above so that the sums are reassociated. The easiest way is replacing the outer BT in expandSOP with NonEmpty. Given that the multiplication there is, much like you suggest, liftA2 (<>), this works straight away.
expandFlat :: E a -> E a
expandFlat = cata algS . fmap (cata algP) . cata algSOP
where
algSOP :: EF a (NonEmpty (BT a)) -> NonEmpty (BT a)
algSOP = \case
Var' s -> pure (Leaf s)
Add' x y -> x <> y
Mul' x y -> (<>) <$> x <*> y
algP :: BTF a (E a) -> E a
algP = \case
Leaf' s -> Var s
Branch' x y -> Mul x y
algS :: NonEmptyF (E a) (E a) -> E a
algS = \case
NonEmptyF x Nothing -> x
NonEmptyF x (Just y) -> Add x y
Another option is using any of the other solutions and reassociating the sums in the distributed tree in a separate step.
flattenSum :: E a -> E a
flattenSum = cata alg
where
alg = \case
Add' x y -> apo coalg (x, y)
x -> embed x
coalg = \case
(Add x x', y) -> Add' (Left x) (Right (x', y))
(x, y) -> Add' (Left x) (Left y)
We can also roll flattenSum and expandEvert into a single function. Note that the sum coalgebra needs an extra case when it gets the result of the distribution coalgebra. That happens because, as the coalgebra proceeds from top to bottom, we can't be sure that the subtrees it generates are properly associated.
-- This is written in a slightly different style than the previous functions.
expandDirect :: E a -> E a
expandDirect = cata alg
where
alg = \case
Var' s -> Var s
Add' x y -> apo coalgAdd (Add x y)
Mul' x y -> (apo coalgAdd' . apo coalgMul) (Mul x y)
coalgAdd = \case
Add (Add x x') y -> Add' (Left x) (Right (Add x' y))
x -> Left <$> project x
coalgAdd' = \case
Add (Add x x') y -> Add' (Left x) (Right (Add x' y))
Add x (Add y y') -> Add' (Left x) (Right (Add y y'))
x -> Left <$> project x
coalgMul = \case
Mul (Add x x') y -> Add' (Right (Mul x y)) (Right (Mul x' y))
Mul x (Add y y') -> Add' (Right (Mul x y)) (Right (Mul x y'))
x -> Left <$> project x
Perhaps there is a more clever way of writing expandDirect, but I haven't figured it out yet.

How do you represent nested types using the Scott Encoding?

An ADT can be represented using the Scott Encoding by replacing products by tuples and sums by matchers. For example:
data List a = Cons a (List a) | Nil
Can be encoded using the Scott Encoding as:
cons = (λ h t c n . c h t)
nil = (λ c n . n)
But I couldn't find how nested types can be encoded using SE:
data Tree a = Node (List (Tree a)) | Leaf a
How can it be done?
If the Wikipedia article is correct, then
data Tree a = Node (List (Tree a)) | Leaf a
has Scott encoding
node = λ a . λ node leaf . node a
leaf = λ a . λ node leaf . leaf a
It looks like the Scott encoding is indifferent to (nested) types. All it's concerned with is delivering the correct number of parameters to the constructors.
Scott encodings are basically representing a T by the type of its case expression. So for lists, we would define a case expression like so:
listCase :: List a -> r -> (a -> List a -> r) -> r
listCase [] n c = n
listCase (x:xs) n c = c x xs
this gives us an analogy like so:
case xs of { [] -> n ; (x:xs) -> c }
=
listCase xs n (\x xs -> c)
This gives a type
newtype List a = List { listCase :: r -> (a -> List a -> r) -> r }
The constructors are just the values that pick the appropriate branches:
nil :: List a
nil = List $ \n c -> n
cons :: a -> List a -> List a
cons x xs = List $ \n c -> c x xs
We can work backwards then, from a boring case expression, to the case function, to the type, for your trees:
case t of { Leaf x -> l ; Node xs -> n }
which should be roughly like
treeCase t (\x -> l) (\xs -> n)
So we get
treeCase :: Tree a -> (a -> r) -> (List (Tree a) -> r) -> r
treeCase (Leaf x) l n = l x
treeCase (Node xs) l n = n xs
newtype Tree a = Tree { treeCase :: (a -> r) -> (List (Tree a) -> r) -> r }
leaf :: a -> Tree a
leaf x = Tree $ \l n -> l x
node :: List (Tree a) -> Tree a
node xs = Tree $ \l n -> n xs
Scott encodings are very easy tho, because they're only case. Church encodings are folds, which are notoriously hard for nested types.

How to represent tree with sharing in Haskell

I would like to represent a "tree" of the following shape in Haskell:
/\
/\/\
/\/\/\
/\/\/\/\
` ` ` ` `
/ and \ are the branches and ` the leaves. You can see that starting at any node, following the left path, then the right gets you to the same node as following the right path then the left. You should be able to label the leaves, apply a function of the two decendants at each node, and propagate this information to the root in O(n^2) time. My naive efforts are giving me an exponential run time. Any hints?
It is certainly possible to construct a tree with shared nodes. For example, we could just define:
data Tree a = Leaf a | Node (Tree a) (Tree a)
and then carefully construct a value of this type as in
tree :: Tree Int
tree = Node t1 t2
where
t1 = Node t3 t4
t2 = Node t4 t5
t3 = Leaf 2
t4 = Leaf 3
t5 = Leaf 5
to achieve sharing of subtrees (in this case t4).
However, as this form of sharing is not observable in Haskell, it is very hard to maintain: for example if you traverse a tree to relabel its leaves
relabel :: (a -> b) -> Tree a -> Tree b
relabel f (Leaf x) = Leaf (f x)
relabel f (Node l r) = Node (relabel f l) (relabel f r)
you loose sharing. Also, when doing a bottom-up computation such as
sum :: Num a => Tree a -> a
sum (Leaf n) = n
sum (Node l r) = sum l + sum r
you end up not taking advantage of sharing and possibly duplicate work.
To overcome these problems, you can make sharing explicit (and hence observable) by encoding your trees in a graph-like manner:
type Ptr = Int
data Tree' a = Leaf a | Node Ptr Ptr
data Tree a = Tree {root :: Ptr, env :: Map Ptr (Tree' a)}
The tree from the example above can now be written as
tree :: Tree Int
tree = Tree {root = 0, env = fromList ts}
where
ts = [(0, Node 1 2), (1, Node 3 4), (2, Node 4 5),
(3, Leaf 2), (4, Leaf 3), (5, Leaf 5)]
The price to pay is that functions that traverse these structures are somewhat cumbersome to write, but we can now define for example a relabeling function that preserves sharing
relabel :: (a -> b) -> Tree a -> Tree b
relabel f (Tree root env) = Tree root (fmap g env)
where
g (Leaf x) = Leaf (f x)
g (Node l r) = Node l r
and a sum function that doesn't duplicate work when the tree has shared nodes:
sum :: Num a => Tree a -> a
sum (Tree root env) = fromJust (lookup root env')
where
env' = fmap f env
f (Leaf n) = n
f (Node l r) = fromJust (lookup l env') + fromJust (lookup r env')
Perhaps you can represent it simply as a list of leaves and apply the function level by level until you're down to one value, i.e. something like this:
type Tree a = [a]
propagate :: (a -> a -> a) -> Tree a -> a
propagate f xs =
case zipWith f xs (tail xs) of
[x] -> x
xs' -> propagate f xs'

Resources